#TITLE_ALTERNATIVE# - MALLORY (NIM : 123 07 057), BOP
Computation of gravity anomalies for 2D object has been developed, based on the derivation of gravity field that caused by an arbitrary 3D body. We use the algorithm of these approaches to make 2D gravity forward modeling software. The main idea of creating this software is to allow us to create a synthetic gravity subsurface model and represent the calculated response graphically, fitting it with the real data until the error is minimized. The software was created with MATLAB R2008a GUI (Graphical User Interface). The software itself provides many customizations that can be utilized to facilitate users in forward modeling. Validations of this software are done by distinguishing produced anomaly response with Grav2D Software using synthetic and real data. These validations include error calculation and spectral analysis (wave length analysis) to see how much error produced in creating a model within GUI software. Synthetic model created in rectangular shape using the same parameter. The result shows that the gravity anomaly response is identical and the error is very small. Real data are also used to test the software feasibility for forward modeling process and the result shows that the GUI software worked well in forward modeling for identifying basement variation in gravity exploration stage.